2011
DOI: 10.1016/j.jaapos.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Stability of near stereoacuity in childhood intermittent exotropia

Abstract: Purpose To investigate the course of near stereoacuity in a cohort of children with untreated intermittent exotropia. Methods A total of 95 children aged 2 to 16 years with untreated intermittent exotropia were identified who had measurements of near stereoacuity, using the Preschool Randot (PSR) test on at least two successive examinations, with no intervening treatment. Deterioration was defined as a drop of at least 3 octaves, based on test–retest data. Alternative secondary analyses were performed defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 28 publications
3
31
1
3
Order By: Relevance
“…Pratt-Johnson et al 18 and Aborms et al 19 believed that early surgery should be performed to preserve stereoacuity. They suggested surgical invention at younger than 4 and 7 years, respectively, whereas Holmes et al 12 proposed that one advantage of delaying or avoiding surgery for intermittent exotropia in younger children is avoidance of prolonged consecutive esotropia, with possible risk of permanent loss of stereoacuity. Others proposed that the surgery should be postponed because not all intermittent exotropias deteriorate and some will even resolve spontaneously after several years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pratt-Johnson et al 18 and Aborms et al 19 believed that early surgery should be performed to preserve stereoacuity. They suggested surgical invention at younger than 4 and 7 years, respectively, whereas Holmes et al 12 proposed that one advantage of delaying or avoiding surgery for intermittent exotropia in younger children is avoidance of prolonged consecutive esotropia, with possible risk of permanent loss of stereoacuity. Others proposed that the surgery should be postponed because not all intermittent exotropias deteriorate and some will even resolve spontaneously after several years.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Previous studies have proposed that patients with intermittent exotropia have good near stereoacuity and deteriorated distance stereoacu-ity, 2,11 whereas others 7,8 deemed that near stereoacuity was significantly poor in intermittent exotropia compared to normal patients preoperatively and postoperatively. Holmes et al 12 believed that near stereoacuity is stable and surgery cannot be considered as an effective way to restore near stereoacuity in intermittent exotro-Purpose: To evaluate fusion stereopsis in patients with intermittent exotropia before and after strabismus surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Distance stereoacuity has been commonly used to monitor deterioration of IXT, because it is known to correlate better with the course of IXT than near stereoacuity. [35][36][37] However, Holmes et al 38 reported that monitoring near stereoacuity is reasonable in children with IXT, because the functional importance of near stereoacuity in children, as well as distant stereoacuity, has been clearly established, and younger children are more interested in near works and functional works such as pegboard task, water task, and bead task, which are related to near stereoacuity. 39 In our study, most patients were relatively young children, therefore improvement in near stereopsis is an important result.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently few data on the natural history of intermittent XT, but in a previous study of the course of stereoacuity in children with untreated intermittent XT, we found a very low deterioration rate over a 2-year period. 28 Further data on stereoacuity in the context of the natural history of intermittent XT, as well as following surgery, will be available at the completion of ongoing randomized clinical trials currently being conducted by the Pediatric Eye Disease Investigator Group (clinical trial identifiers: NCT01032330 and NCT01032603). We also need better methods of categorizing children with intermittent XT as having either monofixation or bifixation, and the new Pediatric Vision Scanner may prove useful in this endeavor.…”
Section: Discussionmentioning
confidence: 99%